Achromobacter xylosoxidans endocarditis and septic arthritis in an infant affected by generalized arterial calcification of infancy. Issue 6 (18th December 2015) - Levoy, Craig S.; Hall, David J.; Berman, David
Abstract : Introduction: Achromobacter xylosoxidans is a non-fermentative aerobic Gram-negative bacillus, which most frequently causes nosocomial infections. Endocarditis from the pathogen has only rarely been reported and has a near-fatal outcome without surgical intervention. Case Presentation: We present a case of A. xylosoxidans endocarditis and septic arthritis in an infant affected by generalized arterial calcification of infancy. The patient was successfully treated with 6 weeks of intravenous colistin, meropenem and trimethoprim/sulfamethoxazole. Conclusion: This is the first reported case of colistin used to treat A. xylosoxidans endocarditis. We discuss the antibiotic challenges of treating multidrug-resistant A. xylosoxidans endocarditis in a patient who is not a surgical candidate.